The health of former prisoners of war : results from the medical examination survey of former POWs of World War II and the Korean Conflict - Page, William Frank, 1948- (National Academy Press, 1992)
"Using the results from comprehensive medical examinations, this volume explores the prevalence of disease among former prisoners of war of World War II and the Korean conflict and the relationship between that prevalence and their decades-earlier treatment while in captivity."--Publisher's description